2008
DOI: 10.2478/s11687-008-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Wild carnivores as source of zoonotic helminths in north-eastern Italy

Abstract: SummaryTwo hundreds and sixty red foxes, eighteen badgers and eight stone martens from north-eastern Italy were examined for zoonotic parasites by SCT, with particular attention to Trichinella sp. and Echinococcus multilocularis. No adult worms of E. multilocularis were observed in the intestine of red foxes or mustelids. Out of 223 fox faecal samples analysed by a commercial CA-ELISA, 5.8 % was positive to Echinococcus coproantigens. Trichinella sp. was detected by digestion of muscle in 1.2 % of examined fox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 34 publications
3
20
1
Order By: Relevance
“…In addition, hare faeces were frequently observed close to the tomato plants at the Italian field site and such wild hares have been shown to carry Campylobacter species, an important pathogen causing gastrointestinal infections in humans (Wahlströ m et al, 2003). Zoonotic helminths have been reported in cats, foxes and dogs (Di Cerbo et al, 2008;Habluetzel et al, 2003) and helminth eggs found in soil may therefore originate from such animals and not only from faecal contaminated irrigation water.…”
Section: Faecal Contamination Of Soilmentioning
confidence: 98%
“…In addition, hare faeces were frequently observed close to the tomato plants at the Italian field site and such wild hares have been shown to carry Campylobacter species, an important pathogen causing gastrointestinal infections in humans (Wahlströ m et al, 2003). Zoonotic helminths have been reported in cats, foxes and dogs (Di Cerbo et al, 2008;Habluetzel et al, 2003) and helminth eggs found in soil may therefore originate from such animals and not only from faecal contaminated irrigation water.…”
Section: Faecal Contamination Of Soilmentioning
confidence: 98%
“…The sedimentation and counting technique (SCT) is a necropsy technique originally developed for detection of Echinococcus multilocularis which is only a few millimetres long (Eckert et al, 2001). However, the technique has also been demonstrated to be suitable for the recovery of other helminths (Di Cerbo et al, 2008;Ziadinov et al, 2010;Al-Sabi et al, 2013a). While necropsy will always be the golden standard for determination of prevalence rates, it can only be used for dead animals and may lead to a bias towards certain age groups or diseased individuals.…”
Section: Introductionmentioning
confidence: 98%
“…There are many probable reasons for fluctuations in the hare population in Europe; however, deterioration of animal health strongly influenced by anthropization of landscape seems to be the key factor. Hares suffer considerably from predation, particularly by foxes (Newey et al, 2007;Romig et al, 2007;Di Cerbo et al, 2008;Miterpáková et al, 2009), and the decline was accompanied by a growth in predators in recent years. The population density may also be influenced by different diseases, some of them occurring only locally.…”
Section: Introductionmentioning
confidence: 99%